2002
DOI: 10.1590/s1413-86702002000300002
|View full text |Cite
|
Sign up to set email alerts
|

A six-year follow-up survey of sexually transmitted diseases in Brasilia, the capital of Brazil

Abstract: The notification of sexually transmitted diseases (STD) is a prime component of well-designed public health policy. However, peculiar aspects of STD must be taken into account for the correct management of surveillance activities. Here, we describe the distribution of the most common sexually transmitted diseases among patients attended by the gynecological clinics of the principal public hospitals of Brasilia and the Federal District, Brazilian capital, during six years. A total of 142,158 patients had their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
4
0
3
Order By: Relevance
“…This finding was consistent with that reported by other authors [21]. A survey that included more than 140,000 women in the Federal District, Midwest region of Brazil, found a prevalence of 7.3% [22].…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding was consistent with that reported by other authors [21]. A survey that included more than 140,000 women in the Federal District, Midwest region of Brazil, found a prevalence of 7.3% [22].…”
Section: Introductionsupporting
confidence: 93%
“…A study conducted in the Federal District, (Simões-Barbosa et al, 2002) found a prevalence of 7.3% in a sample of 142,158 women. Infection with T. vaginalis was present in 10% of the inflammatory lesions [22]. In that research, the methodology used was the Pap smear, which has sensitivity for T. vaginalis detection lower than that of the culture method.…”
Section: Discussionmentioning
confidence: 96%
“…Infection in men is often without clinical symptoms, and they actually play the role of the parasite carriers for women. Therefore, simultaneous treatment of both sexual partners (female and male) is recommended and necessary [1,5] . In this study, after the correct diagnosis of the disease, the patient under study and her husband were treated at the same time, causing the symptoms to be ameliorated.…”
Section: Discussionmentioning
confidence: 99%
“…Vaginitis as a vaginal inflammation is one of the most prevalent infectious diseases among patients referring to midwifery clinics. Bacterial vaginosis, candidiasis, and trichomoniasis are the main leading causes of vaginitis [1] . Bacterial vaginosis is the most common cause of vaginal infection, and the second most common form of vaginal infection among people is vaginal candidiasis [1,2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation